Pulmonary hypertension - Handler, Clive E.; Coghlan, Gerry (Oxford : Oxford University Press, 2013)
An accessible reference text to help clinicians in all relevant specialties understand how to diagnose and manage the conditions of pulmonary hypertension and pulmonary areterial hypertension including information on when and whom to refer patients to.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Feb. 4, 2013).
Keywords: Pulmonary hypertension -- Diagnosis; Pulmonary hypertension -- Treatment